Literature Review: Business Ethics and Good Corporate Governance as the Foundation of Financial Performance in the Banking Industry - Kurniawan Prayitno, Heri (Generate Digital Publishing, 2025)
Objective: This study aims to analyze the strategic role of business ethics and Good Corporate Governance (GCG) in supporting long-term financial performance in the banking industry. This study focuses on how ethical integrity and governance structures contribute to stakeholder trust, risk mitigation, and institutional competitiveness. Research Design & Methods: This article uses a systematic literature review method by analyzing and synthesizing findings from the latest empirical studies published between 2020 and 2024. This review focuses on the relationship between business ethics, corporate governance, and financial performance indicators in the banking sector, including conventional and Islamic financial institutions. Findings: These findings reveal that consistent ethical principles and strong GCG practices significantly improve bank stability, operational efficiency, and financial performance. A structured risk management framework and a formal code of ethics strengthen internal control systems and enhance public trust and institutional credibility. Furthermore, integrating sustainability and social responsibility principles contributes to long-term competitiveness. Implications & Recommendations: Banks are advised to institutionalize ethical behavior and governance structures as strategic priorities, rather than merely complying with regulations. Investing in digital governance capabilities and aligning ESG frameworks with operational strategies is critical to ensuring resilience in a rapidly evolving financial landscape. Contribution & Value Added: This study offers a conceptual contribution by consolidating the relationship between ethical integrity, GCG, and financial outcomes in banking. It provides an academic foundation for strengthening ethical governance practices, particularly in emerging markets where stakeholder trust and systemic stability are critical.